Assessment Of Personality Types in An Urban Community of District Dehradun, Uttarakhand Using Introversion- Extroversion Inventory - Madhavi Bhargava; Jayanti Semwal; Ruchi Juyal; Shaili Vyas; Deepshikha Varshney (Medsci Publications, 2015)
Introduction: Personality can be defined as a person's pattern of in- ternal experience and social interaction that arises from his action. The trait of extroversion-introversion is a central dimension of hu- man personality theories. Objectives: To study the difference in personality in adults according to age and sex and the association of education and personality. Methods: The study was conducted in Rishikesh, Dehradun. A judgemental-purposive sampling was done in view of exploratory nature of the study in the region. The personality type of participants was assessed with introversion extroversion inventory by interview method. This inventory consists of 60 items that cover predominant traits of all three personality characteristics, introvert, extrovert and ambivert. Results: Of a total of 298 adults interviewed, 39% were females and 61% were males. It was found that 26% of the participants were ex- trovert, 15% introvert and 59% were ambivert. More males (28%) were extrovert as compared to females (21.4%). Extrovert personality increased with higher education. Conclusion: There is no difference between adult personality traits of males and females of all age groups. Education did not lead to a sig- nificant difference in personality. Studies with larger sample size are required to understand the changing dynamics of adult personality traits.